2010
DOI: 10.1017/s1461145710000738
|View full text |Cite
|
Sign up to set email alerts
|

Blood BDNF concentrations reflect brain-tissue BDNF levels across species

Abstract: Brain-derived neurotrophic factor (BDNF) is involved in synaptic plasticity, neuronal differentiation and survival of neurons. Observations of decreased serum BDNF levels in patients with neuropsychiatric disorders have highlighted the potential of BDNF as a biomarker, but so far there have been no studies directly comparing blood BDNF levels to brain BDNF levels in different species. We examined blood, serum, plasma and brain-tissue BDNF levels in three different mammalian species: rat, pig, and mouse, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
384
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 588 publications
(400 citation statements)
references
References 24 publications
14
384
2
Order By: Relevance
“…Although the source of serum BDNF relevant to depressive symptoms appears to be concentrated in the platelets (Karege et al, 2005a;Lee and Kim, 2009), its functional significance with regard to central BDNF levels remains unclear. In rats, a positive correlation between serum and central BDNF levels is generally observed at baseline, particularly in young animals (Karege et al, 2002;Klein et al, 2011;Sartorius et al, 2009). Following stress or antidepressant treatment, however, such correlation is inconsistent, probably because of conflicting factors such as age or strain of the animals, or the time of analysis (Béjot et al., 2011; Elfving et al, 2010;Kyeremanteng et al, 2012;Luo et al, 2010).…”
Section: Florian Duclot and Mohamed Kabbaj*mentioning
confidence: 99%
“…Although the source of serum BDNF relevant to depressive symptoms appears to be concentrated in the platelets (Karege et al, 2005a;Lee and Kim, 2009), its functional significance with regard to central BDNF levels remains unclear. In rats, a positive correlation between serum and central BDNF levels is generally observed at baseline, particularly in young animals (Karege et al, 2002;Klein et al, 2011;Sartorius et al, 2009). Following stress or antidepressant treatment, however, such correlation is inconsistent, probably because of conflicting factors such as age or strain of the animals, or the time of analysis (Béjot et al., 2011; Elfving et al, 2010;Kyeremanteng et al, 2012;Luo et al, 2010).…”
Section: Florian Duclot and Mohamed Kabbaj*mentioning
confidence: 99%
“…Second, BDNF and IGF-1 facilitate lipid oxidation in muscles [53] and glucose metabolism [1], which are essential for energy regulation during submaximal activity [54]. Peripheral production of neurotrophins and growth factors can lead to effects on the central nervous system (CNS) because they all cross the blood -brain barrier, resulting in correlated peripheral and CNS concentrations [55]. It is possible that growth factors are upregulated in the periphery for their beneficial effects on metabolic and vascular systems, and then cross the blood -brain barrier, triggering neurogenic actions.…”
Section: (A) Neurotrophins and Growth Factorsmentioning
confidence: 99%
“…Since BDNF crosses the blood-brain barrier in both directions (Pan et al, 1998) and can be measured in serum and plasma (Fujimura et al, 2002), serum BDNF levels may reflect brain BDNF levels (Klein et al, 2011). The first study assessing BDNF in cocaine addicts found no difference in BDNF serum levels in 15 cocaine addicts and a group of healthy controls (Angelucci et al, 2007).…”
Section: Introductionmentioning
confidence: 99%